Respuesta :
Answer: f(0) = g(-4) and f(4) = g(-2)
Step-by-step explanation:
Answer:
=1
Step-by-step explanation:
If the point (a,b)(a,b)left parenthesis, a, comma, b, right parenthesis is on the graph, then g(a)=bg(a)=bg, left parenthesis, a, right parenthesis, equals, b.
We should look for the point on the graph whose xxx-coordinate is -4−4minus, 4.
Hint #22 / 2
The point on the graph whose xxx-coordinate is -4−4minus, 4 is the point (-4,1)(−4,1)left parenthesis, minus, 4, comma, 1, right parenthesis.
Therefore, g(-4)=1g(−4)=1g, left parenthesis, minus, 4, right parenthesis, equals, 1.